2024
DOI: 10.47626/2237-6089-2021-0396
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and safety of cannabidiol-rich cannabis extract in children with autism spectrum disorder: randomized, double-blind, and placebo-controlled clinical trial

Abstract: Objective: Autism spectrum disorder (ASD) is characterized by persistent deficits in social communication and social interaction and by restricted and repetitive patterns of behavior. Some studies have shown that substances derived from Cannabis sativa improve the quality of life of children with ASD without causing serious adverse effects, thus providing an alternative therapeutic option. The objective of this study was to evaluate the efficacy and safety of a cannabis extract rich in cannabidiol (CBD) in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
3
21
0
4
Order By: Relevance
“…Similarly, several cohort studies in children using full-spectrum products have demonstrated significant overall improvement in ASD symptoms reported by parents [5254, 56] and clinicians [55, 57]. Specifically, we found that almost half of treated children with ASD showed reduced disruptive behaviour consistent with other studies that have demonstrated improvement in behavioural problems ranging from 32% to 90%, including adaptive behaviours, self-injury and hyperactivity [53, 57, 59]. Social interaction and communication have also significantly improved following treatment with full-spectrum cannabis extract in children with ASD-related symptoms [52, 5557].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similarly, several cohort studies in children using full-spectrum products have demonstrated significant overall improvement in ASD symptoms reported by parents [5254, 56] and clinicians [55, 57]. Specifically, we found that almost half of treated children with ASD showed reduced disruptive behaviour consistent with other studies that have demonstrated improvement in behavioural problems ranging from 32% to 90%, including adaptive behaviours, self-injury and hyperactivity [53, 57, 59]. Social interaction and communication have also significantly improved following treatment with full-spectrum cannabis extract in children with ASD-related symptoms [52, 5557].…”
Section: Discussionsupporting
confidence: 88%
“…The most frequent side-effect in our cohort was related to gastrointestinal symptoms, which were transient and improved with rest by the end of the treatment phase. However, the majority of clinical studies using full-spectrum cannabis extract for the treatment of children with ASD reported mild or transient adverse events frequently related to sleep disturbances [5255, 58, 59], anxiety or irritability symptoms [52, 55, 57, 58] which were absent in our cohort. This might be due to different strains with variable composition of phytocannabinoids and higher doses of THC than our full-spectrum medical cannabis extract with negligible THC (0.08%).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Overall, cannabinoids were well tolerated, with only mild adverse effects. These promising effects were corroborated in another recent RCT, including N = 60 children with ASD demonstrating significant improvements in social interaction, anxiety, psychomotor agitation, number of meals a day, and concentration after treatment with a CBD-rich cannabis extract at a concentration of 0.5 % (5 mg/mL) in a 9:1 ratio of CBD:THC (daily dose ranged from 6 to 70 drops) [63].…”
Section: Autism Spectrum Disorder (Asd)supporting
confidence: 53%